Évaluer l'impact des stéréotypes dans les supports multimédia - Joëlle Aden (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
Surfing on the Internet offers modern language teachers a kaleidoscope of varied and authentic media reflecting multi-perspective viewpoints on the socio-cultural reality of the groups using the language being learned. Surfing is probably one of the most developed uses of the multimedia in the mass teaching of languages. One need only skim through the textbooks published during the past five years to see that multimedia tools are called on especially in order to research themes studied in class, and many papers have put forth the potential of those tools. In class, the idea that students must be allowed to surf through hypertext without any guidance very quickly gave way to the need to bring access to Internet resources back into well-defined frameworks, usually starting from sites pre-selected for the purpose in order to carry out tasks in the language studied. At present, two types of ICT (information and communication technologies) set-ups play a leading role in language training for teachers, i.e. webquests and e-mail exchanges, but once again, the limitations of webquests are perceptible, as they re-create form-related constraints inside which the reference points are pre-determined. In this article, we examine a set-up integrating freer activities involving both surfing and the choice of video media, which we have reintegrated into a cultural approach in class. We consider the way in which the variety of these media, both free and pre-determined, influence the building of the students' reference points in matters of identity. We will study this phenomenon in connection with the cognitive and socio-discursive mechanisms that learners implement when they are exposed to such media in one and the same teaching set-up, both in and outside class.